The long-term direct and external effects of Jewish expulsions in Nazi Germany - Mevlude Akbulut-Yuksel; Mutlu Yuksel (Institute for the Study of Labor (IZA), 2011)
This paper provides causal evidence on long-term consequences of Jewish expulsions in Nazi Germany on the educational attainment and political outcomes of German children. We combine a unique city-level dataset on the fraction of Jewish population residing in Germany before the Nazi Regime with individual survey data from the German Socio-Economic Panel (GSOEP). Our identification strategy exploits the plausibly exogenous city-by-cohort variation in the Jewish population in Germany as a unique quasi-experiment. We find that the persecution of Jewish professionals had significant, long-lasting detrimental effects on the human capital and political development of Germans who were at school-age during the Nazi Regime. First, these children have 0.4 fewer years of schooling on average in adulthood. Second, these children are less likely to go to college or have a graduate degree. Third, they are less likely to have interest in politics as adults. These results survive using alternative samples and specifications, including controlling for Second World War, Nazi and Communist Party support and unemployment effects.
urn:nbn:de:101:1-201107283768
Keywords: I21; I12; J24; N34; 330; human capital formation; dismissal; Jewish professionals; political development